Visual fixation in NBA free-throws and the relationship to on-court performance - Laby, D. (Journal of Sports and Performance Vision, 2020)
Purpose: Although hitting a baseball is often described as the most difficult task in all of sports, shooting baskets during a game likely ranks a close second. Previous studies have described the role of vision in basketball and more specifically a concept termed the "quiet eye" has been shown to be related to basketball performance. How a shooter visualizes the target, how consistent their visual fixation is, and how long they maintain that fixation has been correlated to shooting success. Although the majority of previous reports have included non-professional basketball shooters, we evaluated NBA (National Basketball Association) players to determine if this skill was significant at the professional level.